2021
DOI: 10.1038/s41598-021-98852-6
|View full text |Cite
|
Sign up to set email alerts
|

Collagen fibers provide guidance cues for capillary regrowth during regenerative angiogenesis in zebrafish

Abstract: Although well investigated, the importance of collagen fibers in supporting angiogenesis is not well understood. In this study, we demonstrate that extracellular collagen fibers provide guidance cues for endothelial cell migration during regenerative angiogenesis in the caudal zebrafish fin. Inhibition of collagen cross-linking by β-Aminopropionitrile results in a 70% shorter regeneration area with 50% reduced vessel growth and disintegrated collagen fibers. The disrupted collagen scaffold impedes endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It is characterized by rays that are aligned in parallel towards the the tip of the tail fin. This also applies to collagen fibers of the extracellular matrix and blood vessels [ 38 ]. Thus, these structural cues are in parallel to the direction of the chemotactic gradient which is generated by tail transection.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by rays that are aligned in parallel towards the the tip of the tail fin. This also applies to collagen fibers of the extracellular matrix and blood vessels [ 38 ]. Thus, these structural cues are in parallel to the direction of the chemotactic gradient which is generated by tail transection.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the extracellular matrix as a possible medium accounting for the positive and negative pattern-setting interactions. Indeed recently, it has been observed that collagen can be re-organized by the growing sprouts, so that it is concentrated around the extending sprouts and depleted elsewhere (19)(20)(21). We explored whether a similar distribution is also be observed for fibronectin, an ECM component that may be consequential to the angiogenesis processes.…”
Section: Fibronectin Distribution May Mediate Sprout Inductionmentioning
confidence: 89%
“…The ECM aids in cell adhesion, cell-to-cell communication, and differentiation (28, 45). In addition to providing matrix structure, collagen fibers guide the growth of capillaries during regeneration (46). In such manner, the microenvironment of the provisional matrix established by FAPs and immune cells serves as the foundation for the regeneration of intact skeletal muscle (25).…”
Section: Discussionmentioning
confidence: 99%
“…Such ambiguity may be attributed to the persistence of basal laminae following efferocytosis, an outcome that prevails in established models (1, 4, 5, 11, 27). Preexisting basal laminae can provide guidance during regeneration of microvessels and myofibers (2831, 46, 47), but a biopsy punch removes the entire tissue. A key finding here is that, in contrast to the concomitant regeneration of microvessels and myofibers discussed above, the onset of microvascular growth into the wound and perfusion across the wound precedes that of myofibers by approximately 1 week.…”
Section: Discussionmentioning
confidence: 99%